Zieve’s syndrome presenting with coagulopathy, skin and subcutaneous haemorrhage - Kondrackienė, Jūratė; Beinaravičienė, Inga; Gelman, Sigita; Kupčinskas, Limas (Acta medica Lituanica, 2013)
Zieve syndrome is characterized by hepatic dysfunction, jaundice, hyperlipidaemia, and reversible hemolytic anaemia after alcohol abuse. We report a rare case of this syndrome presenting with coagulopathy and subcutaneous haemorrhage. Laboratory tests showed macrocytic anaemia, hyperbilirubinemia, increased activity of aminotransferases, hyperlipidemia, coagulopathy, signs of haemolysis: reduced concentration of haptoglobin, free hemoglobin. These abnormalities improved during 20 days. Ultrasonography revealed subcutaneous haemorrhagias, liver biopsy was consistent with steatohepatitis. There are a small number of reported cases of Zieve syndrome, and the reason could be the lack of pathognomonic symptoms, rapid decrease of hyperlipidaemic serum levels after alcohol withdrawal, patients denial of drinking. There is no specific treatment, therapy is similar to that for acute alcoholic hepatitis. The Zieve syndrome must be allways considered in the differential diagnosis of uncertain origin liver injury, hemolysis or coagulopathy.